Etude de la qualité hygiénique et organoleptique de pageot « Pagellus acarne » durant sa conservation. - Louazene, Siham; Boukhatem, Khadidja (My University, 2019)
This study aims at evaluating the organoleptic, microbiological and physicochemical quality of pageot (pagellus acarne) collected at the level of the port and the local market of the city of Mostganem , during its conservation by freezing for a duration of days To test the hypotheses of this study , the microbiological physicochemical and organoleptic analyzes were made on the flesh of the fish in fresh (ambient temperature) and frozen (-4 ° C) while evaluating the physicochemical, microbiological and organoleptic parameters. The result of our study seens thatthe physicochemical analyzes indicate that the pH of the port and the market decreases with the freezing time, the page of the fresh port from 6.88 ± 0.32 to D0 to reach 6.48 ± 0.10 at D15, that of the market of 6.56 ± 0.02to D0 to reach 6.37 ± 0.10 at D15.The microbiological results indicate a significant presence of the FTAM of the order of 1.12 × 10 3 CFU / g on the fresh page of the port and 1.75 × 10 3 for that of the fresh market. These values fall after 15 days of freezing to reach 0.51.10 3 CFU / g and 1.103 CFU / g respectively, to a lesser degree, the same findings were recorded for the other flora analyzed, namely total and faecal coliforms, Staphylococcus aureus. The germs of Clostridium sulphito-reducers and Salmonella sp are completely absent, before and after freezing. The negative cold (-4 ° C) has an inhibitory effect on the bacterial flora present. The organoleptic tests showed that both the port and the market samples, whether fresh or frozen, generally maintained a good state of freshness. In the light of these sobering facts , a set of pedagogical recommendations are suggested .It hopes that our work will serve as a supportive frame for the future researchers whose interest will be close to ours
Keywords: Pageot (Pagellusacarne); freezing; physico-chemical quality; microbiological quality; organoleptic quality